Analisa Gaya Kepemimpinan Kepala Dinas Dalam Meningkatkan Motivasi Dan Profesionalitas Pegawai (Studi Di Dinas Pendidikan Dan Kebudayaan Kota Bima) - Taufikrahman Taufikrahman (Jurnal Ilmiah Mandala Education (JIME), 2020)
. The purpose of this study, namely: (1) evaluating leadership style in increasing employee work motivation in the City of Education and Culture Office of Bima; and (2) evaluating the leadership style in improving the professionalism of employees working in the City of Bima City Education and Culture Office. This research uses a qualitative approach through descriptive analysis. The type of research data in the form of primary data and secondary data. Sources of research data are the head of the department, the head of the ministry of education, the head of the education sector, the head of the PNFI division, the heads of sections, and employees / staff. To get the data source (informant), the researchers used snowball sampling techniques. Data collection techniques using observation, interviews and documentation. While analyzing qualitative data analysis data, which includes: (a) data reduction; (b) data display; and (c) verification (drawing conclusions). Based on the results of the study, the leadership style of the head of the department in increasing the work motivation of Bima City Education and Culture Department employees uses a participative leadership style, which is demonstrated by: understanding the needs of employees at work, giving encouragement work, establish good working relationships, and provide incentives for work performance. Such a leadership style is believed to increase employee motivation in the Bima City Education and Culture Office. Meanwhile, the leadership style of the head of service in improving the professionalism of the employees of the City of Education and Culture (Dikbud) Office of the City of Bima uses a consultative and delegative leadership style, which is demonstrated by way of division of employee work in accordance with the area of expertise, setting measurable work standards, creating a work climate conducive, as well as providing reward and punishment. The applied leadership style can improve the professionalism of employees working at the Bima City Education and Culture Office.